A novel diamide-mesoionic combination insecticide, (Chlorantraniliprole 0.5% + Triflumezopyrim 0.45%) (GR) against stem borer and leaf folder in rice - Kolandhaivelu, Karthikeyan (ORYZA-An International Journal of Rice, 2026)
Field experiments were conducted during the kharif 2020 and rabi 2020-2021 seasons at the Regional Agricultural Research Station, Pattambi, Palakkad, to evaluate the efficacy of diamide and mesoionic insecticide combinations against major insect pests of rice. The treatments included a new combination insecticide, chlorantraniliprole 0.5% + triflumezopyrim 0.45%, applied at 76, 85.5, 95, and 104.5 g a.i. ha-1, along with chlorantraniliprole 0.4% GR @ 40 g a.i. ha-1, triflumezopyrim 10.6% SC @ 25 g a.i. ha-1, and chlorantraniliprole (0.5%) + thiamethoxam (1.0%) GR @ 90 g a.i. ha-1 as standard checks, with an untreated control. Pooled analysis of both seasons revealed that chlorantraniliprole + triflumezopyrim applied at 95 and 104.5 g a.i. ha-1 was most effective in managing yellow stem borer (Scirpophaga incertulas), recording 91.03% and 90.73% reduction in dead heart incidence, respectively, over the control. The same treatments also significantly suppressed leaf folder (Cnaphalocrocis medinalis), with 97.94% and 96.51% reduction in leaf damage. Correspondingly, these treatments resulted in the highest grain yield, with yield increases of 56.00% and 54.14% over the untreated control. The study demonstrates the superior efficacy of the chlorantraniliprole + triflumezopyrim combination for effective pest management and yield enhancement in rice.